The Benefits of Financial Statement Comparability - DE FRANCO, GUS; KOTHARI, S.P.; VERDI, RODRIGO S. (Journal of Accounting Research, 2011)
ABSTRACT Investors, regulators, academics, and researchers all emphasize the importance of financial statement comparability. However, an empirical construct of comparability is typically not specified. In addition, little evidence exists on the benefits of comparability to users. This study attempts to fill these gaps by developing a measure of financial statement comparability. Empirically, this measure is positively related to analyst following and forecast accuracy, and negatively related to analysts? dispersion in earnings forecasts. These results suggest that financial statement comparability lowers the cost of acquiring information, and increases the overall quantity and quality of information available to analysts about the firm.